SANITATION OF FISH FARMS AND PREVENTION OF FISH DISEASES BY POND DRYING WITH THE USE OF FISH AND GRASS ROTATION - A. M. Naumova; A. Yu. Naumova (Российский паразитологический журнал, 2016)
Objective of research: to present the actuality and novelty of application of fish and grass “rotation” because this allows to reveal new data on pond drainage planning which is the most effective in sanitation of the fish farm.Materials and methods: To determine the most effective cycle for the summer drying of ponds, we studied ecological and epizootological features of fishing ponds, which had been used after drying within 1 and 5 years. As research object served 8 fish ponds: 4 drained ponds under crop (40 ha), 4 – overflowed (40 ha) and filled with one-year carps (2,5-З thousand ind./ha) and silver carps (1,2-1,4 thousand ind./ha).Results and discussion: The results of comparative research on anti-epizootic efficacy of pond drying at different periodicity of 1 and 5 years with the use of fish and grass “rotation” are provided. Data on decreased invasion of fishes (carp, silver carp) by parasites, absence of causative agents of infection, improved blood indicators, increased fish production at annual pond drying (with the use of fish and grass “rotation”) compared with the pond drying of 5 year periodicity are presented. Advantages of economic efficacy of the annual frequency of pond drying are confirmed: twice increased commercial fish production; reduced expenses for purchase of food (own barley and wheat production), drugs, disinfectants, fertilizers that allow increasing economic revenue and making profit.